Divorce in the Islamic Legal System, the Continental European System, and the Anglo-Saxon Legal System - Titing Oting Supartini; Ah. Fathonih; Fauzan Ali Rasyid (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2025)
This study examines the comparison of the divorce legal system in three main legal traditions, namely Islamic Law, Continental European Law (civil law), and Anglo-Saxon Law (common law). Divorce as a legal event not only has implications for the breakdown of civil relations between spouses, but also has significant social, psychological, and economic consequences. Each legal system offers a different normative, procedural, and philosophical approach to regulating divorce, both in terms of terms, implementation mechanisms, and protection for vulnerable groups such as women and children. This study uses a comparative legal approach by utilizing Kelsen's theory of legal norms, Pound's theory of the social function of law, and Rawls and Dworkin's concepts of substantive and procedural justice. This analysis aims to describe the differences and similarities in divorce legal approaches in the three systems, as well as evaluate the effectiveness of each system in realizing justice and protection of rights in the context of divorce. This research also emphasizes the importance of harmonizing the principles of justice in divorce regulation in the era of globalization.